2022
DOI: 10.31665/jfb.2022.18312
|View full text |Cite
|
Sign up to set email alerts
|

Improving the oxidation stability of high-oleic sunflower oil with composite antioxidants

Abstract: This study aimed to search for the optimum antioxidant mixture for improvement of the stability of high-oleic sunflower oil. Seven antioxidants including vitamin E, phytic acid, antioxidant of bamboo leaves, rosemary extract, tea polyphenols, ascorbyl palmitate (AP) as well as tea polyphenol palmitate (TPP) were used. Peroxide value, free radicals and Rancimat induction time results all proved that TPP was the best single antioxidant. Therefore, TPP was selected to mix with other antioxidants to form composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Studies have shown that the oxidation stability of high-oleic-acid sunflower seed oil could be significantly improved by the combination of 0.48 g kg −1 tea polyphenol palmitate and 0.04 g kg −1 ascorbic palmitate. 9 However, studies on the combination of natural antioxidants to lengthen the shelf life of unsaturated fatty acid-rich blended oils have not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the oxidation stability of high-oleic-acid sunflower seed oil could be significantly improved by the combination of 0.48 g kg −1 tea polyphenol palmitate and 0.04 g kg −1 ascorbic palmitate. 9 However, studies on the combination of natural antioxidants to lengthen the shelf life of unsaturated fatty acid-rich blended oils have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Although the addition of single antioxidants can enhance the oxidation stability of vegetable oils, the use of combined antioxidants can significantly delay the oxidation of the oils. Studies have shown that the oxidation stability of high‐oleic‐acid sunflower seed oil could be significantly improved by the combination of 0.48 g kg −1 tea polyphenol palmitate and 0.04 g kg −1 ascorbic palmitate 9 . However, studies on the combination of natural antioxidants to lengthen the shelf life of unsaturated fatty acid‐rich blended oils have not been reported.…”
Section: Introductionmentioning
confidence: 99%